Formation and radiative forcing of contrail cirrus - Bernd Kärcher (Nature Portfolio, 2018)
Condensation trails produced by jet aircraft contribute to anthropogenic climate change, yet the magnitude of their impact remains unclear. Here, the author reviews progress in understanding contrails since the last IPCC report (1999), assesses the remaining uncertainty, and identifies potential mitigating options and pathways forward.